The social tourism of the 21st century: a policy for the consumers or the service providers? Analysis of Argentine policy over the period 2000-2015 - Schenkel, Erica (2018)
Given the new conception of social tourism that is taking root internationally, in the 21st century the Argentine government has been reformulating the issue on the public policy level, considering the distributive virtues on which its inclusion on the government agenda have historically been founded, along with economic virtues linked to job and income creation through articulation with the private sector. Focusing on policy analysis, in this study we assess the policy outcomes more than a decade on from implementation, paying special attention to the actors that have benefitted.